Sistem Informasi Beladiri Berbasis Web - Pingkan Kartika Gosal; Agus Lahinta; Nikmasari Pakaya (Gorontalo State University, 2021)
The belt level increase test is a routine activity carried out by Provincial Board (Pengprov) Taekowndo in Gorontalo at every period. The registration process for the taekwondo belt increase test is still done manually by using the registration from on the paper. Additionally, the information regarding Taekwondo (traditional Korean martial arts) in Gorontalo is still less. This research applies a waterfall method, and the design system uses a unified modeling language (UML) deign consisting of a case diagram, activity diagram, sequence diagram, and class diagram. The finding of this research is in the form of martial arts information system that can specifically facilitate the registration process for the taekwondo belt increase test and help get information easily. Besides, this system is tested with black-box and white-box testing and has met the criteria in accordance with the objectives.Keywords: Belt Level Increase Test, Taekwondo, Martial Arts Information System, Waterfall, UML.